1954
DOI: 10.1088/0034-4885/17/1/302
|View full text |Cite
|
Sign up to set email alerts
|

Diffraction Theory

Abstract: A critical review is presented of recent progress in classical diffraction theory.Both scalar and electromagnetic problems are discussed. The report may serve as an introduction to general diffraction theory although the main emphasis is on diffraction by plane obstacles. Various modifications of the Kirchhoff and Kottler theories are presented. Diffraction by obstacles small compared with the wavelength is discussed in some detail. Other topics included are : variational formulation of diffraction problems, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
332
3

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 750 publications
(342 citation statements)
references
References 335 publications
7
332
3
Order By: Relevance
“…This is qualitatively different from the Bethe-Bouwkamp model [51,52] which predicts an electric dipole along the axis normal to the aperture plane. This difference is justified on a symmetry ground due to the conical nature of the NSOM metal coating [45,46] which contrasts with the planar geometry used in the work of Bethe and Bouwkamp.…”
Section: The Aperture Nsom Tipcontrasting
confidence: 87%
See 2 more Smart Citations
“…This is qualitatively different from the Bethe-Bouwkamp model [51,52] which predicts an electric dipole along the axis normal to the aperture plane. This difference is justified on a symmetry ground due to the conical nature of the NSOM metal coating [45,46] which contrasts with the planar geometry used in the work of Bethe and Bouwkamp.…”
Section: The Aperture Nsom Tipcontrasting
confidence: 87%
“…However, there was to our knowledge no use of such a model for describing the NSOM tip emission prior to our own work. Additionally, it should be observed that in complete analogy with the old work by Stratton and Chu (reviewed by Bouwkamp [52]) we can also include in the present description a fictitious density of "magnetic charge" γ and magnetic current K along the rim in order to introduce a net magnetic dipole in the formalism. The formulas for the dipole and fields generated by such magnetic distributions are obtained by analogy with the electric ones (i.e., Eqs.…”
Section: The Aperture Nsom Tipmentioning
confidence: 89%
See 1 more Smart Citation
“…It does not, however, predict several key aspects of coupled wave phenomena. For high frequencyproblems, or equivalently, the situation with large crack size in comparison with wavelength, the KirchhofF approximation [12,13] is applicable if the incident angle is in a restricted range. The basic assumptions involved in the approximation are that the incident field reflects at each point on the defect as though the defect were an infinite plane and the wavefield is zero on the dark side of the crack.…”
Section: Forward Problem and Model Reviewmentioning
confidence: 99%
“…Unfortunately as was shown by Bethe [1] and Bouwkamp [2] the efficiency of such transport is low in the case of subwavelength holes. A remarkable discovery about the transmission of light through a subwavelength hole in a metal screen of a finite thickness and a finite conductivity that has been made by Ebbesen et al [3] has shown that the standard theory of diffraction by small holes is invalid, and, in this case, the transmission of light through the subwavelength hole can be strongly enhanced.…”
mentioning
confidence: 94%